Impact of Demonetization in the Indian Economy: A Review - Ms. Paramjeet Kaur (Ramanujan International Journal of Business and Research, 2017)
Having a wallet full of highest denomination currency is like being at the top of world, but one can't even imagine what will happen if the same currency converts at once in normal blank papers. The boldest move of Prime Minister Modi came up on 8th November in the form of demonetization since he came into power in 2014. Demonetization is tightening the regulatory system in the Indian economy, it is expected change the odds of the game. The move seems to be an appreciable step by the Modi government, as the intention is to stop tax evasion and to uproot corruption. But the side effects in the form of public inconvenience, scams of crores, slum in real estate and other sectors, security issues, effects on GDP can't be overlooked. In the initial days of demonetization majority of the people were supporting the drive, but as the new currency scams were coming up and the length of queues in the banks was not reducing, people were getting frustrated. It seems that demonetization has demoralized Indians. The various scams involving nearly 300-400 crores of new currency have made normal citizen depressed who standing in the long queues was looking at the government with the eyes of hope. Whether demonetization will take the country to new heights or it will snatch the tag of developing country from India, it is still a question. The common man is thinking whether the nation is demonetized or demoralized. The paper discusses the bright as well as dull sides of demonetization drive. It tries to identify the effects of this move on the Indian economy as a whole. The paper is based on descriptive research design and tries to explore the hidden realities.